Multinutritional Blocks in Ruminants: A Strategic Look from Agribusiness through Meta-Analysis - Pacheco Hernandez, Armando; Bonilla-Landaverry, Gesly Anibal (Darul Yasin Al Sys, 2025)
The production of ruminants in grazing systems represents a key alternative to achieve sustainable food, since fodder is one of the most economical and natural sources for these animals. However, one of the most critical challenges in many regions of the world are recurring droughts, which limit the availability of grass and affect livestock productivity. Faced with this scenario, multinutritional blocks (BMN) arise as an accessible and effective solution, since they provide energy, protein and mineral supplementation during the dry season, improving the digestibility of fodder and animal performance. This study aimed to carry out a meta -analysis of scientific literature on BMN published since 2017, with emphasis on its use in cattle, sheep, goats, buffalos and other ruminant species, both for the production of meat and milk. Data collection was carried out through the Scopus and Google Scholar platforms, using inclusion criteria focused on scientific articles focused on the formulation and application of BMN, and excluding thesis, technical articles, interviews and non -scientific materials. The results suggest that, although there is evidence of the benefits of BMN, there is still a significant need for deeper research in this field. This technology represents a strategic tool to improve the profitability of the agricultural sector, especially in climate stress contexts.